Perseus: An Interactive Curriculum on Classical Greek Civilization, A Proposal to the Annenberg/CPB Project - Crane, Gregory; Mylonas, Elli; Martin, Thomas; Nagy, Gregory; Heinrichs, Albert; Hemans, Frederick; Morell, Kenneth; Marchionini, Gary; Smith, D. Neel (Tufts Archival Research Center, 2005)
Traditionally, students of the humanities have encountered barriers in their learning. The primary sources of their studies are often physically inaccessible and difficult to assimilate. In Perseus, therefore, we have begun to use the technology of interactive computing and the dense storage capacity of optical disk to create a vast, highly cross-referenced database of textual and visual information, and to experiment with ways to let the user explore this information. Perseus promotes active learning and, we believe, has already begun to alter the three-way relationship between teacher, student, and source material.